Spillovers Produktivitas Pekerja di Jawa Tengah - Joko Susanto; Didit Welly Udjianto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
This study analyzes the productivity spillovers of workers in the Central Java region. Research data includes worker productivity, capital, and district / city minimum wages in 2017 published by the Central Statistics Agency (BPS). This study uses a spatial regression analysis tool by including the element of worker productivity spillovers and is estimated using Geoda software. The results showed that there were no worker productivity spillovers between districts / cities in Central Java. The value of the Lambda coefficient, on the Spatial Error Model and the Spatial Lag Model is not significant, indicating that the value of worker productivity in each district / city has no influence from the surrounding area. Furthermore, the significant capital variable indicates that an increase in the amount of capital is followed by an increase in worker productivity. Meanwhile, the variable of the number of workers with college graduates is not significant.